Improvement of Mechanical Properties of Aluminium Nano Composites Reinforced with Zirconia Nano Particle - Mahvi Malik Shahzad, Dr.Muhammad Ramzan, Shahid Ali, Faisal Ansari, Karan Sharma (International Journal of Advanced Science and Technology, 2020)
Aluminium alloys are mostly used in aeronautical and automobile industries due to their less density and good mechanical properties, good corrosion resistance and wear, less coefficient thermal of expansion as compared to other metals and metal alloys. The better mechanical properties of these materials and relatively less production cost make them attractive for a various applications both  scientific and technological point of view. The objective behind the designing of metal matrix composite materials is to combine the desirable properties of metals and Ceramics.Present work is focused on the study of behaviour of Aluminium Alloy 6061 with Zirconium dioxide (Zirconia) composite produced by the stir casting technique.Various percentage of reinforcement is used. Tensile test, Hardness Test, Impact test performed on the samples obtained by the stir casting process.The results shows that all the mechanical properties goes on increasing.